AKTIVITAS HIPOGLIKEMI DARI TEH HERBAL CAMPURAN HERBA SAMBILOTO (Andrographis Paniculata) DAN BIJI MAHONI (Swietenia Mahagoni) DAN PROFIL METABOLIT SEKUNDER TAHUN 2022 - Dewi, Hasna (Politeknik Tiara Bunda, 2022)
Diabetes mellitus is a chronic metabolic disorder that continues to present a major world wide health problem. Numerous herbal drugs like Andrographis paniculata and Swietenia mahagoni have been used by people of various cultures to treat diabetes. The aim of this research was to measure the hypoglycemic activity herbal tea of Andrographis paniculata herbs and Swietenia mahagoni seeds and their combination in alloxan- induced diabetic mice. The tea was prepared by brewing 10 g herbal tea with 100 ml of boiling water for 10 minutes. The herbal tea of Andrographis paniculata herbs, Swietenia mahagoni seeds, combination with ratio 1:1, 1:2 and 2:1 (0.4 ml/20 g BW), was administered orally to groups I, II, III, IV and V respectively. The reference drug glibenclamide (0,013 mg/10 g BW) and CMC-Na were also administered orally to animals in positive and negative control group respectively. Oral administration of herbal tea for seven days resulted in a slight reduction in blood glucose level. Statistically there is no groups that has significant difference with negative control groups (P < 0.05) except positive control. Therefore the herbal tea combination of Andrographis paniculata herbs and Swietenia mahagoni seeds with ratio 2:1, showed the biggest reduction in blood glucose level (88.20 ± 43.16 mg/dl). The secondary metabolite profiling was done by establish the TLC and chromatogram profile. TLC profiling was performed out using Chloroform:Methanol (9:1) as mobile phase. Then, TLC plate scanned in wavelength 254 nm and 366 nm using CAMAG TLC Scanner 3.